DOI: 10.11606/d.58.2009.tde-19032010-121015
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos microscópicos do ácido acetilsalicílico (aspirina) e do acetaminofeno (tylenol) na movimentação dentária induzida e nas reabsorções radiculares associadas

Abstract: Maldonado,VB. Microscopic effects of Acetylsalicylic Acid (Aspirin) and Acetaminophen (Tylenol) on induced dental movement and root resorption associated [Dissertação]. Ribeirão Preto: FORP-Universidade de São Paulo; 2009. This study aimed at analysing the influence of acetylsalicylic acid and acetaminophen on induced dental movement and associated root resorption at cell and tissue levels by means of optic microscopy. The experimental groups consisted of 18 rats receiving physiological saline solution; 36 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In 2009, Fracalossi et al 6 suggested a standardization of cross-sectional cuts of murine molars for the analysis of phenomena associated with induced tooth movement, and Santamaria Jr 22 described a practical way to quantify it. Still in 2009, Maldonado 19 investigated the effect of medications, particularly analgesic and anti-inflammatory drugs, on induced tooth movement and the frequency and severity of associated induced tooth movement.…”
Section: Palavras-chavementioning
confidence: 99%
“…In 2009, Fracalossi et al 6 suggested a standardization of cross-sectional cuts of murine molars for the analysis of phenomena associated with induced tooth movement, and Santamaria Jr 22 described a practical way to quantify it. Still in 2009, Maldonado 19 investigated the effect of medications, particularly analgesic and anti-inflammatory drugs, on induced tooth movement and the frequency and severity of associated induced tooth movement.…”
Section: Palavras-chavementioning
confidence: 99%
“…Based on reports found in the literature and the behavior of orthodontic clinical cases within the framework advanced by Maldonado 34 the authors developed the following hypothesis:…”
Section: Fundamentals and Assumptionsmentioning
confidence: 99%
“…3,18 When administered to control pain and discomfort after activation of the orthodontic appliance, what would be the influence of ASA and acetaminophen on tooth movement and the root resorption associated with it? To help in clarifying this question, Maldonado 34 and his team set out to quantitatively determine the influence of ASA and acetaminophen on induced tooth movement and on root resorption by means of optical microscopy. In another study they described the history and action mechanisms of these two medications.…”
mentioning
confidence: 99%
“…It is an oral administration drug, intestinal absorption, rapid distribution, with half-life of 4 hours, metabolized in the liver and excreted by the renal route. 6 Only in 1939 was it approved by the Food and Drug Administration (FDA), being considered prototype and compared to all other non-steroidal anti-inflammatory drugs (NSAIDs). It is part of this group of drugs that act by inhibiting cyclooxygenase (COX) enzymes, causing a reduction in the synthesis of prostaglandins, which results in desirable and undesirable clinical-pharmacological events.…”
Section: Introductionmentioning
confidence: 99%